Eco-human rights: Believer perspective, ethical issues and justice in the Andean context - Irarrázaval, Diego (1999)
In Peru -and in the world- the effort for human rights is expanding. Economic, social, cultural, religious, ecological issues have been added to civil and political affairs... Even today, the rights of women, youth, and children are marked. All these endeavors have new content, if we value the Andean way of being "human" and of correlating with the environment and with the sacred. These concerns have as framework and immense process of transformations that many call globalization and change of era.